Analysis of Tax Amnesty Developments in Indonesia - Hasbi Assidiki Mauluddi; Hasanuddin Hasanuddin; Sahrullah Sahrullah; Nur Widyawati; Alamsjah Alamsjah (Budapest International Research and Critics University, 2022)
This study aims to analysis of tax amnesty developments in Indonesia during the period 1984 to 2018. The research analysis uses a qualitative descriptive approach. Overall data used in this study is secondary data obtained from the results of systematic recording in the form of time series data. The results of the study show that tax amnesty in Indonesia has been successful in terms of the amount of funds received, especially those from declarations, but less successful in terms of repatriation..